An Examination of Washington State Workers' Compensation Claims for Home-Based Health Care Workers, 2006 to 2016: Part 2. Injury Rates and Trends. Issue 3 (August 2022) - Howard, Ninica L.; Adams, Darrin; Marcum, Jennifer; Cole, Jena
Research of home-based health care (HBHC) has shown that care providers suffer from a high rate of injuries. Analysis of workers' compensation records, a reliable source for injury and illness data, enables the identification of trends within a specific working population. HBHC workers' compensation compensable claims in Washington State from 2006 to 2016 were compared to clinical health care (CHC) claims. Injury event and source attributed to HBHC claims were also analyzed, with a focus on work-related musculoskeletal disorders (WMSDs). Though CHC had 5 times the number of full-time employees during the study period, HBHC grew by 61.1%, compared to 28.7% in CHC. Claim rates for all compensable claims and WMSD claims consistently decreased year-over-year for both HBHC and CHC. WMSD claims experienced a year-over-year decline of 5.3%; for all compensable claims the decline was 4.5%. Analysis of HBHC claim rates by injury event found WMSD had the highest rates, followed by falls from the same level. However, the largest annual change was for the injury event overexertion (−10.1%, 95%CI: −13.4, −6.8). HBHC injuries attributable to the health care patient were the most common. Claims with this injury source declined annually by 6.0%. Claim rates for injuries to the back region, and specifically back WMSDs, were consistently higher year-over-year compared to other body regions and WMSD types. Claims for injuries to the back declined by an annual rate of 6.6% (95% CI: −7.9, −5.3), while back WMSD claims decreased by 6.4% (94% CI: −7.8, −4.9).